The effects of relative cycling intensity on saddle pressure indexes - Holliday, W.; Fisher, J.; Swart, J. (Journal of Science and Medicine in Sport, 2019)
Objectives: To compare pressure load and distribution in various saddle zones through a range of workloads in order to provide clinicians and bike fitters with a better understanding of how to optimise saddle positioning. Design: Experimental, quantitative study. Methods: Saddle pressure of seventeen male well-trained cyclists was recorded at 60, 80 and 90% of maximal heart rate, based on data collected during a peak power output test. Results: Loaded area increased significantly and progressively with increased workload while mean pressure did not change significantly. Point of load indexes in longitudinal and transverse planes both increased significantly and progressively with increases in workload. Distribution of load did not change with intensity. Conclusions: Saddle pressure mapping should ideally be performed at an intensity similar to that which the cyclist will encounter during the majority of their training and racing. Comparative measurements of saddle pressures should also standardise workload intensity to ensure reliability of these measurements.